The Effect of Home Visits on Depression and Anxiety in Pregnant Patients During COVID-19 - Lalita, Elisabeth MF; Pratiwi, Dian; Donsu, Amelia; Olii, Nancy (JURNAL INFO KESEHATAN, 2024)
Depression and anxiety during pregnancy can increase the risk of miscarriage, premature birth, low birth weight, low Apgar scores, and fetal death The past COVID-19 pandemic caused significant anxiety and infection fear, causing significant harm to pregnant women's lives. Public access to health services has changed during the COVID-19 pandemic. This study aimed to determine the effectiveness of pregnancy care home visits on depression and anxiety of pregnant women. Efforts should therefore be made to increase visits by pregnant women while maintaining health protocols during the pandemic. The research method is a Quasi-experimental design with one group pretest-posttest design. Sampling was carried out by purposive sampling with the inclusion criteria of pregnant women who did not re-examine at the Health Center for 1 month and pregnant women who were willing to be selected as respondents. obtained 28 pregnant women as respondents. The instruments used are the Edinburgh Postpartum Depression Scale (EPDS) questionnaire and the Hamilton Anxiety Rating Scale (HARS). The data analysis technique used the Paired Simple T-test. The results of the study showed that there was an increase in depression and anxiety during pregnancy during the COVID-19 pandemic, this data was obtained from interviews and pregnancy care with home visits. The depression rate at the initial data of 12.36 dropped to 3.50, and the anxiety rate of 22.46 dropped to 6.61 after being given prenatal care with home visits. In these difficult times, the need for prenatal health care can ensure the provision of protective and safe services and psychological screening of pregnant women at risk for depression to reduce long-term negative outcomes should be carried out.